Christian Missions and Humanitarianism in The Middle East, 1850-1950 Ideologies, Rhetoric, and Practices - Marie Okkenhaug, Inger; Sanchez Summerer, Karène (Leiden Studies in Islam and Society, 2020)
From the early phases of modern missions, Christian missionaries supported many humanitarian activities, mostly framed as subservient to the preaching of Christianity. This anthology contributes to a historically grounded understanding of the complex relationship between Christian missions and the roots of humanitarianism and its contemporary uses in a Middle Eastern context. Contributions focus on ideologies, rhetoric, and practices of missionaries and their apostolates towards humanitarian-ism, from the mid-19th century Middle East crises, examining di􀀃ferent missionaries, their society's worldview and their networks in various areas of the Middle East. In the early 20th century Christian missions increasingly paid more attention to organ-isation and bureaucratisation ('rationalisation'), and media became more important to their work. The volume seeks to discover and retrace such 'entangled histories' for the 􀀄􀀅rst time in an integral perspective. Readership: Those interested in the modern and contemporary history of the Middle East, in religious studies, international relations, scholars, students and practitioners of humanitarianism.